2012
DOI: 10.1108/17570971211253711
|View full text |Cite
|
Sign up to set email alerts
|

Futile search for a better life? Two biographical case studies on women with depression and video game dependency

Abstract: Purpose -Video game dependency (VGD) is a behavioural addiction on the rise with considerably higher prevalence among males, and the rates and patterns of comorbidity with other disorders seem to be comparable to that of substance-related addictions. The purpose of the paper is to investigate the role of gaming behaviour and gaming motives in the biographical context for female addicts with this new type of dual diagnosis.Design/methodology/approach -The authors conducted semi-structured biographical interview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Studies related to this model have also revealed that people who score high on the neuroticism subscale have a personality characterized by feelings of guilt, being easily flustered, low self-esteem, and insecurity in relationships with others [ 9 , 10 , 11 , 12 ]. They are people who carry out a negative self-assessment of themselves [ 13 ] and who present fluctuations in the state of self-esteem—that is, they show instability in self-esteem [ 14 ]. In addition, neuroticism is linked to a greater sensitivity to social evaluations, which means that people with a high level of neuroticism react more intensely to situations in which they are negatively judged by others [ 15 ] since they are more concerned with how others might see them, which in turn might cause stronger reactions to different perceptions of social inclusion [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies related to this model have also revealed that people who score high on the neuroticism subscale have a personality characterized by feelings of guilt, being easily flustered, low self-esteem, and insecurity in relationships with others [ 9 , 10 , 11 , 12 ]. They are people who carry out a negative self-assessment of themselves [ 13 ] and who present fluctuations in the state of self-esteem—that is, they show instability in self-esteem [ 14 ]. In addition, neuroticism is linked to a greater sensitivity to social evaluations, which means that people with a high level of neuroticism react more intensely to situations in which they are negatively judged by others [ 15 ] since they are more concerned with how others might see them, which in turn might cause stronger reactions to different perceptions of social inclusion [ 16 ].…”
Section: Introductionmentioning
confidence: 99%